Loyalitas Pelanggan: Digital Marketing Dan Costumer Perceived Value Terhadap Kepuasan Pelanggan Terhadap - Ismaila Tompo (Jurnal Mirai Management, 2022)
Loyal customers are a target that must be owned by every company. This type of research is a type of quantitative research. By using a cross sectional approach. This study used the Non Probability Sampling technique by purposive sampling. With a total sample of 125 respondents. The analytical method used in this research is "Path Analysis". The results show that digital marketing and Customer Perceived Value have a positive and significant effect on customer loyalty at PT. Catur Putra Harmonis Alauddin Makassar branch either directly or when mediated by customer satisfaction Keywords: Digital marketing, Customer, perceived Value, satisfaction, loyalty